Analysis of the Added Value of Moringa Leaves in Moringa Tea: Case Study at UD Wuna Bharakati, Lupia Village Kabangka Subdistrict, Muna Regency - Ali, La; Fyka, Samsul Alam; Yusriadin (International journal of technology and education research, 2025)
This research aims to identify the value added obtained from processing moringa leaves into moringa tea at UD. Wuna Bharakati, Lupia Village, Kabangka District, Muna Regency. This research was conducted from March to July 2025 using primary and secondary data types and sources. The data analysis used to determine the value added from processing moringa leaves into moringa tea employs the Hayami method of value added analysis. The results of the study indicate that the value added obtained from processing moringa leaves into moringa tea products is Rp419,360/kg, where this value consists of business profit or processing of Rp416,060 and labor remuneration of Rp3,300. The return on the largest factor of production ownership is 93.4% of the business profit, while labor income is 0.74% and contributions from other inputs are 5.7%.